Greenland, Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
July 29, 1931. Kaiser Franz Josef Fjord. Curious cloud or fog rising up from water along south side of fjord near Isfjord. Photo taken looking S.S.W. from S.S. Veslekari.